Pengembangan User Interface Pada Website Geopark Belitong - Dedi Haryanto; Apriansyah Apriansyah; Wempy Pirgana (UNIVERSITAS INDO GLOBAL MANDIRI)
The more advanced the times, the more new things are found and one of them is world heritage. This world heritage can be in the form of geological heritage, cultural heritage, heritage, biological heritage, etc. This arises from the human initiative to find new things which then this heritage will be preserved and maintained. Then the various heritages are processed and preserved through Geoparks. An Earth Park (Geopark) is a single or combined geographic area, which has a Geological Heritage Site (Geosite) and valuable landscapes, related to aspects of Geological Heritage (Geoheritage), Geological Diversity (Geodiversity), Biodiversity (Biodiversity), and Cultural Diversity (Cultural Diversity), and managed for conventional purposes, education, and sustainable community economic development with the active involvement of the community and local government, so that it can be used to foster public understanding and concern for the earth and the surrounding environment. throughout the world without exception, and all under the auspices of UNESCO. UNESCO is an abbreviation of the United Nations Educational, Scientific and Cultural Organization) or the United Nations Educational, Scientific and Cultural Organization which was founded in 1945. The purpose of the organization is to support peace and security by promoting cooperation between countries through education, science and culture in order to increase mutual respect based on justice, the rule of law, human rights, and essential freedoms. To Improve the Belitong Geopark Information Center Has a Website to provide information to the public globally. From the analysis of the Geopark Website, there are several layouts and color choices that do not fit well. Therefore, through this research, a User Interface was developed on the Geopark Website so that it is easy to use by users, has a good User Experience and has a good user interface quality. Keywords: Geopark, Unesco, PBB, User Interface, User Experience